Untranslatability Found in J.K. Rowling’s English Novel Harry Potter and The Sorcerer’s Stone and Its Indonesian Version - Mayra Susanti; Novalinda Novalinda (English Department, Faculty of Humanities, Andalas University, 2017)
This research is about the problem of untranslatability in the translation of novel Harry Potter and the Sorcerer’s Stone by J.K. Rowling. The intention is what are the types of untranslatability, the causes and how the translator solves the problem of untranslatability that happen in this novel. From 27 data, the researcher finds two types of untranslatability in the novel Harry Potter and the Sorcerer’s Stone by J.K. Rowling: linguistic untranslatability and cultural untranslatability. Then there are nine causes of untranslatability found in the novel. The cause is dominated by the culture-specific words or phrases which are semantically complex. From the analysis, it is found that the translator tend to use the loan word or loan word plus explanation strategy to solve the problem of untranslatability in this novel.